Implementasi asas keterbukaan dalam pelaksanaan konseling individu pada siswa SMA - Nuning Kurniawati; I Ketut Dharsana; Kadek Suranata (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2023)
The principle of openness is the basis for success in the counseling process. Individual counseling process in order to help students solve their problems. The implementation of individual counseling services provided has a responsibility that is adjusted to the counselor's duties with the services provided. In addition to being a place for learning and providing good learning services, it also provides guidance and counseling services that are formed in the procurement of several school programs. Thus, the implementation of Guidance and Counseling services for high school students also has a distinctive characteristic, namely counselors who provide counseling services by applying the principle of openness, especially in the implementation of individual counseling. This article study aims to find out how the role of counselors in using the principle of openness to counselees and to find out how counseling influences high school students. sourced from reputable articles and books, with 2 strong sources relevant to research conducted with the keywords "Principle of Openness" and "Individual Counseling". The results show that the implementation of individual counseling services in high schools applies the principle of openness as an effective strategy in exploring information about student problems. The results obtained, students or counselees feel more confident and comfortable during consultations to solve problems as well as possible with the guidance of a counselor